2011
DOI: 10.1148/radiol.11101638
|View full text |Cite
|
Sign up to set email alerts
|

T1ρ MR Imaging Is Sensitive to Evaluate Liver Fibrosis: An Experimental Study in a Rat Biliary Duct Ligation Model

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.11101638/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
135
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(150 citation statements)
references
References 25 publications
(19 reference statements)
11
135
3
Order By: Relevance
“…The biophysical mechanism underlying T1rho MRI is thought to be related to the proton exchange and dipole-dipole interactions between the free water pool and macromolecules (such as collagen and proteoglycan [29]). Increased T1rho has been reported in animal models of liver fibrosis with the degree of fibrosis correlated with the degree of increase in T1rho measurements [15]. Chronic kidney disease (CKD) due to LN is characterized by the progressive loss of kidney function resulting from chronic tubulointerstitial injury, which encompasses tubular atrophy and interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biophysical mechanism underlying T1rho MRI is thought to be related to the proton exchange and dipole-dipole interactions between the free water pool and macromolecules (such as collagen and proteoglycan [29]). Increased T1rho has been reported in animal models of liver fibrosis with the degree of fibrosis correlated with the degree of increase in T1rho measurements [15]. Chronic kidney disease (CKD) due to LN is characterized by the progressive loss of kidney function resulting from chronic tubulointerstitial injury, which encompasses tubular atrophy and interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…T1rho MRI is another emerging MRI technique that is sensitive to the presence of macromolecules (such as collagen and proteoglycan [14]). A preclinical study in a rat biliary duct ligation (BDL) model demonstrated that T1rho imaging detected liver fibrosis in BDL rats and that the degree of fibrosis correlated with the degree of increase in T1rho measurements [15].…”
mentioning
confidence: 99%
“…The first is that our technique did not completely suppression micro-vessel blood signal in rat liver. Additional respiration gating was not used in the study, however, as previous studies on rat liver T1ρ imaging (32) and rat liver CEST (38) showed this was not an important obstacle as in rats liver is tightly attached to the posterior wall of the abdominal cavity [for example, image 5 of reference (32), where free breathing is allowed while high quality T1ρ mapping was obtained]. It is highly possible that if respiration gating is applied and further technique improvement is used to fully suppress blood signal in liver, blood signal suppression can be more successful, then the normal liver T1ρ value range will be narrower, and the diagnosis of early liver fibrotic changes can be made with even more confidence.…”
Section: Bdl Is a Well Established Model For Liver Fibrosis Researchmentioning
confidence: 99%
“…With a biliary duct ligation-induced liver fibrosis rat model, we reported that T 1 r MRI is able to detect liver fibrosis, and the degree of fibrosis is correlated with the degree of elevation of the T 1 r measurements [14]. Additionally, our recent study demonstrated T 1 r MRI can be used to assess liver fibrosis induced with CCl4 intoxication of 1 ml kg -1 twice weekly.…”
mentioning
confidence: 93%